Pengembangan Sistem Booking Online pada Barbershop Mr. Klimis Berbasis Website Menggunakan QR Code untuk Meningkatkan Efisiensi Layanan Bisnis - Habi Tri Surya Ananda; Hendry; Zulfahmi Syahputra (CV. Hawari, 2026)
The rapid development of information technology has encouraged service businesses to improve service quality through the digitalization of business processes. Mr. Klimis Barbershop still manages service reservations and customer queues manually, resulting in long waiting times, recording errors, and increased administrative workload. This study aims to develop a web-based online booking system integrated with QR Code technology to improve business service efficiency at Mr. Klimis Barbershop. The system was developed using the System Development Life Cycle (SDLC) with the Waterfall approach, consisting of requirements analysis, system design, implementation, testing, and maintenance stages. The application was built using the Laravel framework and provides features such as barber selection, service time slot selection, queue management, automatic booking code generation, and an administrative dashboard. QR Code technology is implemented as a quick access medium to the booking system, enabling customers to make reservations more conveniently. System testing was conducted using the Black Box Testing method to ensure that all functionalities operated according to user requirements. The results indicate that the developed system simplifies the reservation process, improves queue management, reduces administrative workload, and enhances service quality and operational efficiency at Mr. Klimis Barbershop.